1988
DOI: 10.1063/1.454972
|View full text |Cite
|
Sign up to set email alerts
|

A tractable molecular theory of flow in strongly inhomogeneous fluids

Abstract: A recently introduced model is used to study several flows in fluids with large density variations over distances comparable to their molecular dimensions (strongly inhomogeneous fluids). According to our model, the local average density model (LADM), local viscosity coefficients can be assigned at each point in a strongly inhomogeneous fluid and the stress tensor retains its Newtonian form provided that the properly defined local viscosities are used. The model has been previously shown to agree with the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
124
2
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(133 citation statements)
references
References 18 publications
5
124
2
2
Order By: Relevance
“…Though this might be a good assumption for macroscopic systems, it is questionable at molecular dimensions. Measurements with the SFA [994][995][996][997] and computer simulations [998][999][1000] showed that the viscosity of simple liquids can increase many orders of magnitude and liquids can even undergo a liquid-to-solid transition when being confined between solid walls separated only few molecular diameters; water seems to be an exception [1001,1002]. Several experiments also indicated that isolated solid surfaces induce a layering in an adjacent liquid and that the mechanical properties of the first molecular layers are different from the bulk properties [78,724,725,1003].…”
Section: Introductionmentioning
confidence: 99%
“…Though this might be a good assumption for macroscopic systems, it is questionable at molecular dimensions. Measurements with the SFA [994][995][996][997] and computer simulations [998][999][1000] showed that the viscosity of simple liquids can increase many orders of magnitude and liquids can even undergo a liquid-to-solid transition when being confined between solid walls separated only few molecular diameters; water seems to be an exception [1001,1002]. Several experiments also indicated that isolated solid surfaces induce a layering in an adjacent liquid and that the mechanical properties of the first molecular layers are different from the bulk properties [78,724,725,1003].…”
Section: Introductionmentioning
confidence: 99%
“…Further, while no relation between fluid properties and the partial viscosity has yet been established, we propose that i w i , where is the shear viscosity of the mixture and w i is the weight fraction of species i. This result is obtained by requiring that for a uniform fluid the total shear stress on all of the components is that on the mixture as a whole, i.e., P n i 1 i d v i =dr d v=dr, where v is the mass average mixture velocity.For the nonuniform nanopore fluid, the transport properties i and D ij are nonlocal properties, expressed as functions of locally averaged densities, following the local average density model [7,11,12]. Equation (1) may be PRL 100, 236103 (2008) …”
mentioning
confidence: 99%
“…For the nonuniform nanopore fluid, the transport properties i and D ij are nonlocal properties, expressed as functions of locally averaged densities, following the local average density model [7,11,12]. Equation (1) may be PRL 100, 236103 (2008) …”
mentioning
confidence: 99%
“…It is worth noting that Newton's law of viscosity is not valid for systems where the channel width is very small, i.e. smaller than 6-7 molecular diameters [12,18]. In this case the shear viscocity varies considerably in the system and Newton's law breaks down: The shear viscocity may exhibiting singularities and even become negative [19].…”
Section: The Stream Velocitymentioning
confidence: 99%
“…One might argue that this is a drawback of the truncation. It is very interesting to note, however, that these modulations are also observed in NEMD simulations of Couette and Poiseuille flows for small channel widths [18,12]. It would be necessary to make very long molecular dynamics simulations in order to increase the signal-to-noise ratio and to determine if the modulations are also present at the nanoscale.…”
Section: The Stream Velocitymentioning
confidence: 99%